Analisis Perlakuan Akuntansi Aset Biologis Menurut Psak 69 Dengan Pendekatan Nilai Wajar - Maulida, Dewi Nur; Leniwati, Driana; Juanda, Ahmad; haryanti, Agustin Dwi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to determine the suitability of disclosure, measurement, and recognition of biological assets to PSAK 69. The novelty of the research lies in the object of research where the object of this research was taken from one of the many cattle farmers in the village of Cukal. To find out the purpose of this study using descriptive qualitative method analysis by interviewing and obesrvasi on Abdi farm cattle farms located in Bakal village, Pujon district. The results of this study state that in terms of measurement, Abdi farm has used fair value when buying and selling assets that are in accordance with PSAK 69. However, the disclosure of biological assets on Abdi farm has not been in accordance with PSAK number 69 because there is no written record of the transactions that occurred. The recognition of biological assets on Abdi farm is in accordance with PSAK 69 because Abdi farm has recognized agricultural products from biological assets owned by Abdi farm, namely milk as its supply.